153 D-DIMER STABILITY OF SPECIMENS STORED AT -20 AND -70 DEGREES CELSIUS. (1st January 2005) - Fabre, A.; Blacklock, L.; Crookston, K.; Libby, E.; Garcia, D.
Abstract : Background: Cross-linked fibrin degradation products known as d-dimers are commonly used to evaluate the likelihood of thromboembolism in clinical and research settings. Currently, frozen samples of platelet-poor plasma are stored at -70 degrees C for later use in research and quality-control. Demonstration of d-dimer stability in plasma stored at -20 C could diminish the cost of storing these samples. Purpose: The purpose of this study was to determine whether d-dimer concentration is as stable at -20 C as at -70 C, when stored for as long as 6 months. Methods: Citrated platelet-poor plasma samples were collected from 20 male and 16 female asymptomatic volunteers, and baseline d-dimer concentrations were determined using the STA®-Liatest® D-Di. Aliquots from these 36 samples were stored at -20 C and -70 C for d-dimer measurement at 1, 3, and 6 months after collection. Comparison of d-dimer level was done by subtracting the baseline value for each individual from their subsequent observed values. Each individual's changes from baseline were then analyzed using paired Student's t-test, repeated measures analysis of variance, or multiple linear regression as appropriate. Results: There were 216 samples; d-dimer concentrations ranged from 0.01 to 1.08 mcg/ml. The changes in d-dimer difference over time were not significantly different for the two storage temperatures (p=0.29). The observed differences were small and unlikely to be of clinical importance. (Table ) Conclusion: This study demonstrates that platelet-poor plasma can be stored for up to 6 months at -20 C rather than -70 C without significantly altering the stability of d-dimer concentration as measured by the STA®-Liatest® D-Di.